Interpersonal communication and contraception: Insights and evidences from Bangladesh demographic and health survey, 2011 - Manoj Kumar Raut (Wolters Kluwer Medknow Publications, 2015)
This paper examines the role of exposure to mass media and interpersonal communication in predicting the current use of contraception in Bangladesh. Bivariate and multivariate analyses were carried out using the Bangladesh Demographic and Health Survey (BDHS), 2011 data to explore the association between communication and the current use of contraception. After adjusting the related socioeconomic and demographic factors, the mass media did not seem to have any role in predicting contraceptive use behavior while the findings revealed that interpersonal communication [prevalence ratio (PR): 1.0984, 95% confidence interval (CI) 1.0801-1.1170] is a strong positive predictor of the current contraceptive use. It is a well-known fact that mass media performs only the knowledge function while interpersonal communication performs an additional function of persuasion. This analysis corroborates the statement that the role of interpersonal communication is quite important in predicting contraceptive use.